Integrasi Sejarah Lokal Tower Air Belanda dalam Pembelajaran Sejarah - munira, widia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
History is understanding and learning that can create those who understand history, face the past and see a better future. Therefore, the use of local historical heritage can convey historical value as part of inculcating student character. This study aims to introduce the historical learning of the historical heritage of Pidie Regency. The method used in this research is descriptive and qualitative through direct visits to the location, which is done by obtaining historical objects at the location of the